2020
DOI: 10.1128/jb.00219-20
|View full text |Cite
|
Sign up to set email alerts
|

Novel Functions and Signaling Specificity for the GraS Sensor Kinase of Staphylococcus aureus in Response to Acidic pH

Abstract: Although the GraS sensor kinase of Staphylococcus aureus is known for sensing of and resistance to cationic antimicrobial peptides (CAMPs), we recently established that it also signals in response to acidic pH which is encountered on human skin concurrently with CAMPs, antimicrobial unsaturated free fatty acids (uFFA), and calcium. We therefore evaluated how these environmental signals would affect GraS function and resistance to antimicrobial uFFA. Growth at pH 5.5 promoted increased resistance of S. aureus U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 71 publications
4
17
0
Order By: Relevance
“…This work highlights the critical importance of the GraXRS regulatory system and the Gra-regulated mprF gene as a resistance system against innate immune effectors. Previous work has shown that GraS is able to sense acidic pH, such as that of human skin, or the phagolysosome of macrophages and respond through GraR-mediated upregulation of resistance genes, such as mprF , allowing for bacterial survival ( 29 , 31 , 43 ). However, as stated previously, it is known that synovial fluid from osteoarthritis patients has a neutral pH of approximately 7.35 ( 14 ), so GraS must sense some factor or condition, possibly CAMPs, in the synovial fluid other than the pH in order to respond through GraR-mediated gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…This work highlights the critical importance of the GraXRS regulatory system and the Gra-regulated mprF gene as a resistance system against innate immune effectors. Previous work has shown that GraS is able to sense acidic pH, such as that of human skin, or the phagolysosome of macrophages and respond through GraR-mediated upregulation of resistance genes, such as mprF , allowing for bacterial survival ( 29 , 31 , 43 ). However, as stated previously, it is known that synovial fluid from osteoarthritis patients has a neutral pH of approximately 7.35 ( 14 ), so GraS must sense some factor or condition, possibly CAMPs, in the synovial fluid other than the pH in order to respond through GraR-mediated gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Direct interaction of the EL loop region (DYDFPIDSL) with CAMPs is also likely in S. aureus , since a soluble EL mimic of GraS protected S. aureus against CAMP-mediated death [ 53 ]. The proline at position 39 and the two aspartic acid residues at positions 37 and 41 located within the EL are important for full GraS activity [ 53 , 54 , 55 ].…”
Section: Grarsmentioning
confidence: 99%
“…Recent work has expanded the sensory capabilities of GraS to include the sensing of acidic pH [ 54 , 55 , 59 ], and GraS activation at low pH is mandatory for survival within macrophages [ 58 ]. Interestingly, pH-dependent modulation of GraS activity seems to be independent of the Gra-EL implicated in CAMP sensing [ 58 ].…”
Section: Grarsmentioning
confidence: 99%
See 1 more Smart Citation
“…The xylose-inducible promoter system is repressible by glucose ( Wieland et al, 1995 ), which also prohibits its use in in vivo studies, as glucose is a common constituent inside mammalian cells. The tetracycline-inducible promoter system is currently the most functional inducible system for gene expression in S. aureus ( Bateman et al, 2001 ; Harrison et al, 2019 ; Goncheva et al, 2020 ; Kuiack et al, 2020 ). However, the inducers such as tetracycline or anhydrotetracycline required in this system, in our experience, affect the normal metabolism of or are even toxic to S. aureus , which results in undesirable phenotypes.…”
Section: Introductionmentioning
confidence: 99%